Joint submission endorsing the inclusion of food systems in the outcome of the first global stocktake of the Paris Agreement - CGIAR Initiative on Low-Emission Food Systems (2023)
The CGIAR Initiative on Low-Emission Food Systems has contributed to a submission in response to a call for views from UNFCCC parties and non-party stakeholders on the elements for consideration of the outputs component of the first global stocktake of the Paris Agreement.